Control Room - Noujaim, Jehane (United States : Noujaim, Jehane Jehane Noujaim, 2004)
If ever a film could be termed incendiary, it's "Control Room." Helmed by 29-year-old Egyptian-American filmmaker, it scans the inner workings of Al Jazeera and comes up with a balanced view of the Arab satellite news agency, even suggesting it might traffic more in truth than the western news media. That takes cojones -- Al Jazeera, with its 40 million Arab viewers, is routinely demonized in America as "Osama bin Laden's mouthpiece." Officials here get riled by the network's "inflammatory" counter narrative, which has the nerve to foreground the suffering of the war's Arab victims, broadcasting graphic visuals of the ongoing carnage. Cutting back and forth between American broadcasters and Al Jazeera, the film lays out the divergent ways the war was reported by the Arabs and the West. Example: the toppling of Saddam's statue, according to the Arab channel, was orchestrated as an American media event, with teen participants who were not even Iraqis. Despite its incendiary aura, though, Noujaim's film, a standout at Sundance and Lincoln Center's New Directors/New Films, is less political broadside than a riveting account of how the news is created and packaged. It chronicles the chroniclers, zooming in on a cast of complex characters who rarely fail to enlighten and surprise.
Duration: 01:23:00
Keywords: Documentary films